The Role of the Soa Head in Social Interaction in the Waenalut Village Community, Namrole District, South Buru Regency - Lesnussa, Dika Diana (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The aim of this research is to find out the role of the head of social interaction in the community. The type of research used is descriptive research with a qualitative approach. The data collection technique in this research is interviews which are used to obtain information by asking informants directly using interview guidelines in accordance with The problem being researched is that research documentation obtains data by collecting data sourced from archival written data and images relating to the role of the SOA head in social interaction. This is one of the villages that implements the role of the SOA head in social interaction. The cultural values of citizenship are social values, togetherness values, religious values and moral values. All these values are reflected in the lives of the people of Waenalut village.